Optimalisasi Sistem Pemidanaan Anak Berkeadilan: Analisis Pendekatan Restoratif dan Diversi di Indonesia - Adelia Nindya Kirana; R. Rahaditya (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The Law on the Juvenile Justice System in Indonesia has been designed to prioritize the protection of children through the implementation of restorative and diversion approaches. The primary aim of this approach is to enable children involved in legal issues to be reintegrated into society and to have a better chance for their future. However, data shows that many juvenile criminal cases end with imprisonment, which contradicts the goals of this Law. Therefore, it is necessary to optimize the juvenile justice system to achieve fair sentencing. This research employs a normative legal method with a descriptive-analytical approach and utilizes a statutory approach to analyze the Law and related regulations. Data was collected through literature study, including both primary and secondary data. The analysis was conducted qualitatively to provide a comprehensive understanding. Diversion, as a restorative justice effort, serves to protect children and resolve cases outside the formal judicial process, while the author emphasizes the need for improvements in the rehabilitation of juvenile offenders to prevent reoffending.